Skate the world : photographing one world of skateboarding - Mehring, Jonathan (National Geographic, 2015)
A collection of two hundred photographs of professional skateboarders, including Tony Hawk, Nyjah Huston, Eric Koston and more. Includes photos from New York to Hong Kong to Istanbul and beyond.